Finding Voice: A Visual Arts Approach to Engaging Social Change - Berman, Kim (The New Public Scholarship, 2018)
In Finding Voice, Kim Berman demonstrates how she was able to use visual arts training in disenfranchised communities as a tool for political and social transformation in South Africa. Using her own fieldwork as a case study, Berman shows how hands-on work in the arts with learners of all ages and backgrounds can contribute to economic stability by developing new skills, as well as enhancing public health and gender justice within communities. Berman's work, and the community artwork her book documents, present the visual arts as a crucial channel for citizens to find their individual voices and to become agents for change in the arenas of human rights and democracy.